Metabolomic and flux‐balance analysis of age‐related decline of hypoxia tolerance in Drosophila muscle tissue - Laurence Coquin; Jacob D Feala; Andrew D McCulloch; Giovanni Paternostro (Molecular Systems Biology, 2008)
Abstract The fruitfly Drosophila melanogaster is increasingly used as a model organism for studying acute hypoxia tolerance and for studying aging, but the interactions between these two factors are not well known. Here we show that hypoxia tolerance degrades with age in post‐hypoxic recovery of whole‐body movement, heart rate and ATP content. We previously used 1H NMR metabolomics and a constraint‐based model of ATP‐generating metabolism to discover the end products of hypoxic metabolism in flies and generate hypotheses for the biological mechanisms. We expand the reactions in the model using tissue‐ and age‐specific microarray data from the literature, and then examine metabolomic profiles of thoraxes after 4 h at 0.5% O2 and after 5 min of recovery in 40‐ versus 3‐day‐old flies. Model simulations were constrained to fluxes calculated from these data. Simulations suggest that the decreased ATP production during reoxygenation seen in aging flies can be attributed to reduced recovery of mitochondrial respiration pathways and concomitant overdependence on the acetate production pathway as an energy source.